Economic Impact of Advanced Pediatric Cancer on Families - Bona, Kira (2013)
CONTEXT: Despite emerging evidence of substantial financial distress in families of children with complex illness, little is known about economic hardship in families of children with advanced cancer. OBJECTIVES: To describe perceived financial hardship, work disruptions, income losses and associated economic impact in families of children with advanced cancer stratified by federal poverty level (FPL). METHODS: This is a cross-sectional survey of 86 parents of children with progressive, recurrent or non-responsive cancer at three children’s hospitals. Seventy-one families with complete income data (82%) are included in this analysis. RESULTS: Parental work disruptions were prevalent across all income levels, with 67 (94%) families reporting some disruption. At least one parent quit a job because of the child’s illness in 29 (42%) families. Nineteen (27%) families described their child’s illness as a great economic hardship. Income losses due to work disruptions were substantial for all families; families at or below 200% FPL, however, were disproportionately affected. Six (50%) of the poorest families lost more than 40% of their annual income as compared with two (5%) of the wealthiest families (P=0.006). As a result of income losses, nine (15%) previously non-poor families fell from above to below the 200% FPL. CONCLUSION: The economic impact of pediatric advanced cancer on families is significant at all income levels, although poorer families suffer disproportionate losses. Development of ameliorative intervention strategies is warranted.